Facilitating participation in cardiovascular preventive initiatives among people with diabetes: a qualitative study - Marie Dahl; Susanne Friis Søndergaard; Axel Diederichsen; Frans Pouwer; Susanne S. Pedersen; Jens Søndergaard; Jes Lindholt (BMC, 2021)
Abstract Background Type 2 diabetes (T2D) is associated with a significantly increased risk of cardiovascular disease (CVD). The DIAbetic CArdioVAscular Screening and intervention trial (DIACAVAS) was designed to clarify whether advanced imaging for subclinical atherosclerosis combined with medical treatment is an effective strategy to develop individualised treatment algorithms for Danish men and women with T2D aged 40-60. But in the DIACAVAS pilot study, the uptake was only 41%. Consequently, we explored how people experienced living with T2D to understand how to improve the uptake in initiatives targeting the prevention of CVD. Methods We used semi-structured interviews to obtain information on how the respondents experienced having T2D. For supplementary information, we used structured interviews on e.g. socioeconomic factors. From April to October 2019, 17 participants aged 40-60 years were recruited from general practices and diabetes outpatient clinics in Denmark. Several levels of analysis were involved consistent with inductive content analysis. Results The participants' experiences of living with T2D fell along two continuums, from an emotional to a cognitive expression and from reactive to proactive disease management. This led to identification of four archetypal characteristics: (I) powerlessness, (II) empowerment, (III) health literacy, and (IV) self-efficacy. These characteristics indicated the importance of using different approaches to facilitate participation in cardiovascular preventive initiatives. Additionally, findings inspired us to develop a model for facilitating participation in future preventive initiatives. Conclusion Encouraging people with T2D to participate in cardiovascular preventive initiatives may necessitate a tailored invitation strategy. We propose a model for an invitational process that takes into consideration invitees' characteristics, including powerlessness, empowerment, health literacy and self-efficacy. This model may enhance participation in such initiatives. However, participation is a general concern, not only in relation to cardiovascular prevention. Our proposed model may be applicable in preventive services for people with T2D in general.